Tanggung Jawab Penyedia Layanan Aplikasi Marketplace Terhadap Konsumen Dalam Transaksi Jual Beli Online di Provinsi Jambi - Indri Winarsih; Firya Oktaviarni (Zaaken: Journal of Civil and Business Law, 2021)
The purpose of this study was to determine the responsibilities of market application providers to consumers in online buying and selling transactions in Jambi Province. In answering this problem, the authors use a research method with an empirical juridical approach. The data obtained were analyzed qualitatively and then presented descriptively. The results of this study indicate that market providers are responsible for providing a means of reporting or complaints and following up on problems, bridging in solving problems between sellers or sellers in the market and consumers and are responsible for the implementation of their electronic systems even though they are not maximally as expected, obligations and responsibilities. marketplace providers to consumers in online buying and selling transactions in Jambi Province on the obligations and responsibilities in Law Number 80 of 2019 concerning Trade through Electronic Systems, Circular of the Minister of Communication and Information Technology Number 5 of 2016 concerning Limitations of Platform Providers and Merchants (Merchants) Trading through Electronic Systems (Electronic Commerce) in the form of User Generated Content (UGC) as well as consumer rights in Law Number 8 of 1999 concerning Consumer Protection. Abstrak Tujuan penelitian ini adalah untuk mengetahui mengenai tanggung jawab penyedia aplikasi marketplace terhadap konsumen dalam transaksi jual beli online di Provinsi Jambi. Dalam menjawab masalah tersebut penulis mengguanakan metode penelitian dengan pendekatan yuridis empiris. Data yang diperoleh dianalisis secara kaualitatif dan kemudian disajikan secara deskriptif. Hasil penelitian ini menunjukan bahwa penyedia marketplace bertanggung jawab dalam menyediakan sarana pelaporan atau pengaduan dan menindaklanjuti permasalahan, menjembatani dalam  penyelesaian permasalahan antara penjual atau seller dalam marketplace dengan konsumen dan bertanggungjawab atas penyelenggaraan sistem elektroniknya meskipun belum secara maksimal seperti yang diharapkan, kewajiban dan tanggung jawab penyeda marketplace  terhadap konsumen dalam transasksi jual beli online di Provinsi Jambi  pada dasarnya meliputi kewajiban dan tanggung jawab dalam Undang Undang Nomor 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik, Surat Edaran Menteri Komunikasi dan Informatika Nomor 5 Tahun 2016 tentang Batasan Penyedia Platform dan Pedagang (Merchant) Perdagangan Melalui Sistem Elektronik (Electronic Commerce) yang berbentuk User Generated Content (UGC) serta hak konsumen dalam Undang Undang Nomor 8 Tahun 1999 Tentang Pelindungan Konsumen.